2019
DOI: 10.1021/acs.jafc.9b01567
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Anthocyanin Rutinosides after Consumption of a Blackcurrant (Ribes nigrum L.) Extract

Abstract: The dominant anthocyanins in blackcurrant are delphinidin-3-O-rutinoside and cyanidin-3-O-rutinoside. Data on their absorption and distribution in the human body are limited. Therefore, we performed a human pilot study on five healthy male volunteers consuming a blackcurrant (Ribes nigrum L.) extract. The rutinosides and their degradation products gallic acid and protocatechuic acid were determined in plasma and urine. The rutinosides' concentrations peaked in both plasma and urine samples within 2 h of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
4
25
1
Order By: Relevance
“…Moreover, sucralose was the sweetener that provided the highest bioavailability for most compounds (CA, CAT, THBA, and TIFA derivatives, DHPAA-sulfate, HA and VA-glucuronide-sulfate), followed by stevia (DHPAA, HA-sulfate, and VA-sulfate). Sucrose did not provide a remarkably higher bioavailability of any compound as compared with sucralose or stevia, due to intestinal sugar carriers, which may play an important role in flavonoid absorption [29]. A study carried out by Mülleder et al showed that the addition of sucrose to juices decreased the total excretion of anthocyanins [30].…”
Section: Assessment Of the Concentration Of Anthocyanins Metabolites mentioning
confidence: 98%
“…Moreover, sucralose was the sweetener that provided the highest bioavailability for most compounds (CA, CAT, THBA, and TIFA derivatives, DHPAA-sulfate, HA and VA-glucuronide-sulfate), followed by stevia (DHPAA, HA-sulfate, and VA-sulfate). Sucrose did not provide a remarkably higher bioavailability of any compound as compared with sucralose or stevia, due to intestinal sugar carriers, which may play an important role in flavonoid absorption [29]. A study carried out by Mülleder et al showed that the addition of sucrose to juices decreased the total excretion of anthocyanins [30].…”
Section: Assessment Of the Concentration Of Anthocyanins Metabolites mentioning
confidence: 98%
“…There are many reports suggest that AC are absorbed directly (without any metabolization) and then distributed in the blood before being excreted intact into the urine [18,19,20]. BCA consists mainly of AC rutinosides, which have higher bioavailability compared to AC monoglucoside precursors.…”
Section: Bca Properties Bioavailability and Distribution In Eye Tmentioning
confidence: 99%
“…The total excreted amount was calculated: 0.040% (Dp3rut) and 0.048% (Cy3rut) of the ingested doses. In addition, after consumption of the anthocyanin-rich extract, the concentration of the main metabolite, protocatechuic acid, increased significantly [54].…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 97%
“…The maximum concentration in the plasma was reached in 0.3 and 0.5 h, respectively, while the maximum concentration of anthocyanins from blueberry powder was reached in 4 h. Interestingly, the maximum anthocyanin concentration in plasma varied from 1.4 to 591.7 nM and did not depend on the administered dose, which was possibly due to differences in the anthocyanin composition in various foods. Recently, a human pilot study was performed by Rȯhrig and colleagues [54] on five healthy male volunteers who were consuming anthocyanin-rich blackcurrant extract. They studied the kinetics of the dominant anthocyanins-Dp3rut and Cy3rut-in plasma and urine after the consumption of blackcurrant extract.…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%